PENGARUH KUALITAS FITUR, DESAIN, IKLAN, KEPUASAN KONSUMEN DAN KEBUTUHAN MENCARI VARIASI TERHADAP KEINGINAN BERPINDAH MEREK HANDPONE (Survai Pada Pengguna Handphone Di Kota Purwokerto) - Andry Irawan; Nurhayati Indyastuti; Suliyanto Suliyanto (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2010)
The background of this research is that there is intense competition in the mobile industry and the still limited research examining brand displacement. This research was conducted on 110 mobile phone users in Purwoketo. Analysis tools used in this study is Stuctural Equation Modelling (SEM). The results of this study is the variable quality of features, design and advertising have a positive influence on satisfaction. Variables positively influence satisfaction of the needs for information and consumer loyalty. Variable needs to find information in a positive impact on customer loyalty.